Enhancing conceptualisations of information behaviour contexts through insights from research on e-dictionaries and e-lexicography - Bothma, Theo JD; Fourie, Ina (Information Research an international electronic journal, 2024)
Introduction. Extensive conceptualisations of context in information behaviour research do not extend to all contexts revealed in the use of electronic (e)-dictionary and similar e-sources. Information behaviour emphasises users’ contexts and their situations. As intermediaries, examples of using e-dictionaries reveal additional contexts. E-dictionary research and lexicographical insight add additional conceptualisations of information behaviour contexts. Method. Conceptual paper drawing on literature reviews of research on e-dictionaries and conceptualisations of information behaviour contexts, and an exemplar approach to e-dictionary use. Analysis. The literature and dictionary use examples are analysed through an information behaviour lens with added lexicographic insight. Results. Conceptualisations of context in information behaviour research strongly focus on the user (e.g. the need, problem) and specific situations in such contexts, sometimes extending to temporality and spatiality. Information retrieval literature also notes the context of the person who created information and of an intermediary (person or system). Three contexts are evident from e-dictionary use and lexicography: user, information intermediary (dictionary), and word, phrase or text (information source). These contexts might influence information behaviour. Conclusion. The use of e-dictionaries and similar intermediaries, observed with lexicographic insight, can enhance conceptualisations of context in information behaviour, which is of value in the use of information sources and information evaluation.